Pathway MCQs as an Active Learning Strategy for Students in Microbiology: A Preliminary study - Jessica Dâ€™Souza, Anand Kukkamalla, Shobha K.L and (Recent Research in Science and Technology, 2011)
Medical curriculum involves many pathways. Understanding and remembering pathways in Microbiology (esp. pathogenesis) is a challenging task for the students.Ã‚Â Pathway MCQ (Dugdale AE, 1998) helps in eliminating this confusion. An effort was made to introduce these Pathway MCQs as a teaching, revising and as an evaluation strategy to enable them to remember the pathways more effectively thereby enhancing understanding of concepts. A total of 106 second year medical students of Melaka Manipal Medical College (Manipal Campus) were included in this study. Pathway MCQs (PMCQs) on specific topics were prepared by the faculty members. Initially, the students were asked to answer the questions in the form of short answer on few topics prior to administration of PMCQs. These short essay answers were evaluated. Later, each student was given a set of Pathway MCQs on the topic administered earlier. Students had to solve the PMCQs and write a short answer thereafter. The PMCQs and the short answers were evaluated by faculty members who were not involved in the study. A class test was conducted after 4 weeks on topics assigned in the semester including the topics that were administered as PMCQs. After evaluation, the marks scored by the students were tabulated and analyzed. A feedback in the form of a questionnaire was collected from students. PMCQs were found to be simple and interesting, helped to remember and understand pathways, enhanced active learning, employed as a revising strategy and as a formative evaluation strategy. Statistical analysis suggested that studentsÃ¢â‚¬â„¢ overall performance in examinations had been enhanced after administration of PMCQs.